Performance of Activated Natural Zeolite on Purification of Oil from Tempeh Chips Frying - Ahmadi, Kgs (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Used frying oil is the oil that used repeatedly. This oil has low quality physically and chemically. This research was objected to purify used frying oil from tempeh chips processing therefore it is suitable for consumption. The elucidated factors were HCl normality and zeolite activation temperature. This research used completely randomized design with two factors that arranged factorially. The first factor was HCl normality in zeolite soaking: without soaking (HCl 0 N), and soaking with HCl 2 N, 4 N, and 6 N. The second factor was ziolite activation temperature: 3000C, 4000C, 5000C, dan 6000C.The result showed that HCl normality and zeolite activation temperature were significantly affected the performance of zeolite. The color value, free fatty acid content, and anisidin value decreased as the HCl normality and activation temperature increased. It was supposed that the increasing HCl normality and activation temperature caused the ratio of Si/Al increased. It affected the capability of zeolite for adsorption. Meanwhile, the peroxide value increased as the HCl normality increased due to increasing polarity that caused by increasing Si/Al ratio. The best characteristic of purified used frying oil was obtained from HCl 6 N and activation temperature of 6000C with the characteristic as followed: color value that indicated by absorbance at 500 nm of 0.491, free fatty acid content of 0.5%, peroxide value of 0.094 meq/kg, and anisidine value of 43.92.Keywords: used frying oil, natural zeolite, activation